(untitled) (Applied Biological Research, 2025)
Brodifacoum, a highly potent second-generation anticoagulant, emerges as a powerful solution for controlling rodent populations that have developed resistance to other compounds within its class. This study highlights the comparable efficacy of ready-to-use brodifacoum bait (0.005% BB) and bromadiolone bait (0.005% RB) in managing rodent infestations in both sugarcane and rice cultivation systems.In sugarcane fields, two applications of brodifacoum bait, administered at 15-day intervals in September and November (@ 1 kg ha⁻¹ each), showed nearly equal effectiveness to bromadiolone treatments in reducing rodent populations and crop damage. Similarly, in rice fields, brodifacoum applied 15 days before transplanting (@ 5 g per burrow), followed by a second application before the milky grain stage (@ 1 kg ha⁻¹), also matched the performance of bromadiolone treatments in controlling rodent activity and minimizing damage.These findings strongly support the potential of brodifacoum as a reliable alternative for rodent control, especially in agricultural environments where conventional anticoagulants have limited success.